2012
DOI: 10.5923/j.ijaf.20110101.05
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feed Restriction on Carcass Yield Characteristics and Economic Advantages of Rhode Island Red Pullets

Abstract: Carcass yield characteristics and economic advantage of skip-a-day feed restriction method at different growth stages of Rhode Island Red chicken was evaluated. Two-hundred forty day-old chicks with average body weight of 48.92±1.5 g were randomly distributed into 12 pens each with 20 chicks, representing four feeding regimen of T 1 (Unrestricted, Control), T 2 (Restricted at 7, 14, 21 and 28 days of age), T 3 (Restricted at 35, 42, 49 and 56 days of age) and T 4 (Restricted at 63, 70, 77 and 84 days of age). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
2
2
0
2
Order By: Relevance
“…These data corroborate those reported by Hassanien (2011), Tesfaye et al (2011) and Jalal and Zakaria (2012). However, both forms of feed restriction provided a low breast yield compared to broilers fed ad libitum.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These data corroborate those reported by Hassanien (2011), Tesfaye et al (2011) and Jalal and Zakaria (2012). However, both forms of feed restriction provided a low breast yield compared to broilers fed ad libitum.…”
Section: Discussionsupporting
confidence: 90%
“…Weights and yields of edible organs are similar among broilers with and without feed restriction, regardless of the restriction methodology applied. The results of this study are in agreement with Hassanien (2011), Tesfaye et al (2011), Jalal and Zakaria (2012 and Van der Klein et al (2017). It appears that the organs of the gastrointestinal tract are spared from the effects of food restriction depending on animal age and duration of the restriction period (Ferraris et al, 2001).…”
Section: Discussionsupporting
confidence: 86%
“…The weight of the liver of laying hens increases in the periods prior to laying (Hazelwood et al, 1986) thus the higher relative liver weight may be associated with the precocity of light laying hens, since the onset of reproductive activity of the females implies an increase in the activity of this organ, due to the reason for effective synthesis of available energy to lipid for yolk formation (Tesfaye et al, 2009). The results obtained in this study agree with those obtained by Figueiredo et al (2002) e Marcato et al (2010), who found that commercial strains of broilers with higher metabolic activity showed greater relative liver weight.…”
Section: Resultsmentioning
confidence: 99%
“…Os resultados de rendimento de carcaça e dos cortes nobres mostraram que os programas de restrição alimentar não afetam os componentes da carcaça de frangos. Os resultados deste trabalho parecem indicar que a restrição alimentar de curta duração melhora o desempenho dos frangos mais pela melhoria da eficiência alimentar e menos pelo ganho compensatório, o que é diferente das restrições alimentares de longo prazo o que por ser mais severas que tendem a estimular o ganho compensatório dos frangos (Teimouri et al, 2005;Zhan et al, 2007;Tesfaye et al, 2011;Jalal & Zakaria, 2012e Bortoluzzi et al, 2013. Ocak & Sivri (2008) relataram que durante o período de realimentação os componentes da carcaça respondem mais rapidamente a realimentação do que o corpo inteiro.…”
Section: Rendimento De Carcaça E Cortes Nobres E Peso Da Gorduraunclassified
“…Resultados semelhantes foram colhidos por Novel et al (2009) e Hassanien (2011), que não observaram diferenças significativas no peso do coração e fígado entre os grupos de frangos submetidos a restrição alimentar comparado aos frangos de alimentação ad libitum de ração. Ao contrário, Tesfaye et al (2011) e Jalal & Zakaria (2012, observaram diferenças no peso do fígado entre aves com restrição alimentar e aves do tratamento ad libitum.…”
Section: Peso Dos óRgãos Comestíveisunclassified